2012
DOI: 10.1103/physics.5.43
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Near-Infrared Light Emission in Graphene

Abstract: We show that strongly photoexcited graphene monolayers with 35 fs pulses quasi-instantaneously build up a broadband, inverted Dirac fermion population. Optical gain emerges and directly manifests itself via a negative conductivity at the near-infrared region for the first 200 fs, where stimulated emission completely compensates absorption loss in the graphene layer. Our experiment-theory comparison with two distinct electron and hole chemical potentials reproduce absorption saturation and gain at 40 fs, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These results prompt us to search for other possible mechanisms for macroscopic direct light manipulation. It is well known that graphene sheet shows unique optoelectronic properties due to its Dirac conical and gapless band structure, which allows graphene to: 1) absorb all wavelength of light efficiently, 2) achieve population inversion state easily as a result of the excitation of hot electrons and the relaxation bottleneck at the Dirac point and then 3) eject the hot electrons following the Auger-like mechanism [16][17][18][19][31][32][33] . Many studies of this effect have been reported not only for individual suspended graphene sheets 17,18 but also for reduced graphene oxide sheets 29 .…”
Section: Mechanism Of the Macroscopic And Direct Light Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results prompt us to search for other possible mechanisms for macroscopic direct light manipulation. It is well known that graphene sheet shows unique optoelectronic properties due to its Dirac conical and gapless band structure, which allows graphene to: 1) absorb all wavelength of light efficiently, 2) achieve population inversion state easily as a result of the excitation of hot electrons and the relaxation bottleneck at the Dirac point and then 3) eject the hot electrons following the Auger-like mechanism [16][17][18][19][31][32][33] . Many studies of this effect have been reported not only for individual suspended graphene sheets 17,18 but also for reduced graphene oxide sheets 29 .…”
Section: Mechanism Of the Macroscopic And Direct Light Propulsionmentioning
confidence: 99%
“…A series of control experiments were further carried out, which also excludes the laser beam ablation mechanism. The efficient light absorption of graphene 16,17 and easily achievable reverse saturation state 18,19 , combined with the unique and limited hot electron relaxing mechanisms and channels 17,20 , all due to the unique band structure of graphene, collectively make this bulk graphene material capable of efficiently emitting energetic electrons while it is under light illumination so that the net momentum generated by the ejected electrons can propel the bulk graphene sponge according to Newton's laws of motion.…”
mentioning
confidence: 99%
“…36 In this case, the coupling between the top and bottom graphene layers adds more to the plasmonic resonance bandwidth resulting in high absorption in the previously said frequency range. 25,44,46 The coupling is highest at h = 2.5 μm and the absorptivity response has three resonance peaks in this case that is clear from Figure 6B. The width (q) of the top layer plus-shaped graphene pattern, which is superimposed with the primitive fractal pattern has been undergone several variations.…”
Section: Simulated Results and Discussionmentioning
confidence: 77%
“…The whole 3D structure works as a rectangular cavity in which EM wave enters into it through the top surface and gets reflected from the bottom surface with multireflection demonstrated by Fabry‐Perot resonance 36 . In this case, the coupling between the top and bottom graphene layers adds more to the plasmonic resonance bandwidth resulting in high absorption in the previously said frequency range 25,44,46 . The coupling is highest at h = 2.5 μm and the absorptivity response has three resonance peaks in this case that is clear from Figure 6B.…”
Section: Simulated Results and Discussionmentioning
confidence: 85%